Trichomonas vaginalis adherence phenotypes and extracellular vesicles impact parasite survival in a novel in vivo model of pathogenesis. - Brenda M Molgora; Sandip Kumar Mukherjee; Sharon Baumel-Alterzon; Fernanda M Santiago; Katherine A Muratore; Anthony E Sisk; Frances Mercer; Patricia J Johnson (Public Library of Science (PLoS), 2023)
Trichomonas vaginalis is a human infective parasite responsible for trichomoniasis-the most common, non-viral, sexually transmitted infection worldwide. T. vaginalis resides exclusively in the urogenital tract of both men and women. In women, T. vaginalis has been found colonizing the cervix and vaginal tract while in men it has been identified in the upper and lower urogenital tract and in secreted fluids such as semen, urethral discharge, urine, and prostatic fluid. Despite the over 270 million cases of trichomoniasis annually worldwide, T. vaginalis continues to be a highly neglected organism and thus poorly studied. Here we have developed a male mouse model for studying T. vaginalis pathogenesis in vivo by delivering parasites into the murine urogenital tract (MUT) via transurethral catheterization. Parasite burden was assessed ex-vivo using a nanoluciferase-based gene expression assay which allowed quantification of parasites pre- and post-inoculation. Using this model and read-out approach, we show that T. vaginalis can be found within MUT tissue up to 72 hrs post-inoculation. Furthermore, we also demonstrate that parasites that exhibit increased parasite adherence in vitro also have higher parasite burden in mice in vivo. These data provide evidence that parasite adherence to host cells aids in parasite persistence in vivo and molecular determinants found to correlate with host cell adherence in vitro are applicable to infection in vivo. Finally, we show that co-inoculation of T. vaginalis extracellular vesicles (TvEVs) and parasites results in higher parasite burden in vivo. These findings confirm our previous in vitro-based predictions that TvEVs assist the parasite in colonizing the host. The establishment of this pathogenesis model for T. vaginalis sets the stage for identifying and examining parasite factors that contribute to and influence infection outcomes.